Potential use of gene transfer in athletic performance enhancement - Baoutina, A.; Alexander, I. E.; Rasko, J. E. J.; Emslie, K. R. (Molecular Therapy, 2007)
After only a short history of three decades from concept to practice, gene therapy has recently been shown to have potential to treat serious human diseases. Despite this success, gene therapy remains in the realm of experimental medicine, and much additional preclinical and clinical study will be necessary for proving the efficacy and safety of this approach in the treatment of diseases in humans. However, a potential complicating factor is that advances in gene transfer technology could be misused to enhance athletic performance in sports, in a practice termed "gene doping". Moreover, gene doping could be a precursor to a broader controversial agenda of human "genetic enhancement" with the potential for a significant long-term impact on society. This review addresses the possible ways in which knowledge and experience gained in gene therapy in animals and humans may be abused for enhancing sporting prowess. We provide an overview of recent progress in gene therapy, with potential application to gene doping and with the major focus on candidate performance-enhancement genes. We also discuss the current status of preclinical studies and of clinical trials that use these genes for therapeutic purposes. Current knowledge about the association between the natural "genetic make-up" of humans and their physical characteristics and performance potential is also presented. We address issues associated with the safety of gene transfer technologies in humans, especially when used outside a strictly controlled clinical setting, and the obstacles to translating gene transfer strategies from animal studies to humans. We also address the need for development and implementation of measures to prevent abuse of gene transfer technologies, and to pursue research on strategies for its detection in order to discourage this malpractice among athletes.